Hubungan Stres Pengasuhan Orang Tua dengan Kemampuan Regulasi Emosi Anak pada Masa Pandemi Covid-19 - Heidy Kristikanti; Afra Hafny Noer; Lucia Voni Pebriani (Ilmu Psikologi Universitas Yudharta Pasuruan, 2023)
The COVID-19 pandemic that has lasted for almost 2 years, certainly brought a significant change to human life. This study aims to determine the relationship between parental stress and children’s emotion regulation during the COVID19 pandemic which has been running for a long time. The method in this study uses correlational quantitative methods. The population and sample in this study were parents who has school-age children and participate in online learning during COVID-19. The measuring instrument data was using a Parental Stress Scale (PSS) and The Emotion Regulation Checklist (ERC). Based on data analysis, a correlation value between parental stress and emotion regulation has weak correlation (r: 0,200 – 0,400), but with a significant relationship (Sig <0,50). Meanwhile, a correlation value between parental stress and lability/negativity has a fairly strong relationship (r: 0,400-0,700) and significant (Sig <0,50). This shows that there is no relationship between parental stress and emotional regulation, and also there is a negative relationship between parental stress and the lability/negativity in children